Real Earnings Management And Firm Value: Examination Of Costs Of Real Earnings Management - Alex Johanes Simamora; Atika; Masculine Muhammad Muqorobin (Jurnal Akuntansi, 2022)
The objective of this research is to find the evidence of (1) REM towards firm value and (2) the moderating role of costs of REM which are market share, financial health, and effective tax rate between REM and firm value. Research samples are manufacturing firms listed on the Indonesian Stock Exchange 2018-2020. REM includes abnormal CFO, abnormal production, and abnormal discretionary expenses. Data analysis uses a white regression test. Based on data analysis, REM has a negative effect on firm value which indicates that REM reduces economic value. Market share and financial health weaken the negative effect of REM on firm value, indicating that REM is a signal where the firm has strong industry and financial advantages to increase firm value. The effective tax rate has no moderating effect between REM and firm value, indicating that low effective tax rate can be both efficient tax planning such as tax avoidance and aggressive tax planning such as tax evasion. Research contribution gives academics, financial statement users, and regulatory bodies an additional literature of REM as a signaling tool of industry and financial health advantages.